REVIEW OF DIAGNOSTIC METHODS FOR HELICOBACTER PYLORI ASSOCIATED GASTROINTESTINAL PATHOLOGY IN CHILDREN - Ganieva Sh.Sh; Artikova M.M (Scholar Express Journals, 2022)
The authors conducted a review of modern studies on the diagnosis of diseases of the gastrointestinal tract, non-invasive methods of examination of Helicobacter pylori associated gastrointestinal pathologies. The results of numerous studies by foreign and domestic authors are systematized.
Keywords: Helicobacter pylori; gastrointestinal pathology; saliva; diagnosis